Effects of amino acids on the fermentation of inulin or glucose to produce R, R‐2, 3‐butanediol using Paenibacillus polymyxa ZJ‐9. (1st December 2019) - Gao, J.; Jiang, R.F.; Cao, C.; Ni, H.; Zhang, L.; Deng, L.N.; Xu, H.; Jiang, R.Y.
Abstract: This study investigated the effects of different amino acids on the fermentation of pure inulin and glucose using Paenibacillus polymyxa ZJ‐9 in order to improve the production of R, R ‐2, 3‐butanediol ( R, R ‐2, 3‐BD) respectively. The inulin extract from Jerusalem artichoke tubers contained 19 common amino acids, which were detected by HPLC. Arg featured the highest content (1290 mg l −1 ). A single add‐back experiment of 20 common amino acids indicated that Asn, Ser, His and Arg are key amino acids in R, R ‐2, 3‐BD synthesis during inulin fermentation using P. polymyxa ZJ‐9. The corresponding yields of R, R ‐2, 3‐BD reached 24·32, 22·32, 22·03 and 21·04 g l −1 after the four key amino acids (1·5 g l −1 each) and glucose were evaluated in this fermentation. The yields were considerably higher than that of the control group (12·11 g l −1 ). With the addition of the mixture of four amino acids (1·5 g l −1 each), the highest yields of R, R ‐2, 3‐BD (25·07 and 17·47 g l −1 ) were obtained with the increase of 107·0 and 89·1% during the fermentation of glucose and pure inulin respectively. Significance and Impact of the Study: Paenibacillus polymyxa is a micro‐organism with a reported potential for industrialized production of R, R ‐2, 3‐butanediol. The nitrogen sources have a significant effect on R, R ‐2, 3‐butanediol formation using P. polymyxa . This study demonstrated a highly efficient new method to improve the yield of R, R ‐2, 3‐butanediol without adding other nitrogen sources except amino acids during the fermentation. This will therefore decrease the production cost of R, R ‐2, 3‐butanediol and provide a new strategy for promoting synthesis of amino acid‐dependent products.